An umbrella review of reviews on challenges to meaningful adolescent involvement in health research - Azza Warraitch; Maria Lee; Delali Bruce; Paul Curran; Qusai Khraisha; Ciara Wacker; Joshua Hernon; Kristin Hadfield (Health Expectations)
Abstract Background Less than 1% of studies on child and adolescent health report the involvement of adolescents in health research. This is attributed to barriers experienced by researchers and adolescents in the engagement process. To address this under‐involvement of adolescents, we first need a better understanding of the factors that hinder adolescent involvement in health research. Objective We conducted an umbrella review of reviews to consolidate the review‐level evidence on the barriers to meaningful involvement of adolescents in health research. Methods We preregistered this umbrella review of reviews with PROSPERO (CRD42021287467). We searched 11 databases; Google Scholar; and PROSPERO; supplemented by a hand search of the reference lists of eligible reviews, relevant journals, websites of 472 organisations, and input from experts. This resulted in the inclusion of 99 review articles exploring adolescent involvement in studies on adolescent physical or mental health, which were narratively synthesised. Adolescent coresearchers were engaged at all stages of the review. Results We found that adolescent involvement in health research is impeded by several challenges experienced by researchers and adolescents. Some challenges experienced by researchers were organisational issues which included limited resources, gatekeeping and paying adolescents. Some barriers were related to a lack of preparedness among researchers and included a lack of awareness of adolescent involvement, the need for training and guidance, and negative attitudes towards participatory research. There were also barriers around how adolescents can be involved, such as researchers finding it challenging to adapt to new methods, issues with recruitment and retention of adolescents, inclusiveness and accessibility. There were also challenges specific to adolescents, such as adolescents' skills and expertise, training, motivations and study goals. Finally, barriers related to the ethical involvement of adolescents included issues with power dynamics, confidentiality, safety and protection of adolescents. Some of the barriers reported by adolescents included tokenistic involvement, inaccessibility of adolescent involvement, and their competing demands. Conclusion Researchers may find this review useful in understanding and planning for potential challenges of involving adolescents in research. Despite many identified barriers to adolescent engagement, few mitigation strategies were identified to address these barriers. There is a clear need to establish best practices for meaningful adolescent involvement in health research. Public and Patient Involvement in the Review Adolescents were involved at multiple stages of this umbrella review of reviews. They reviewed the protocol, screened 25% of the articles at title and abstract screening stage, screened 10% of full‐text articles, and worked on data analysis. They also helped plan and conduct a participatory workshop with an adolescent advisory group to discuss the challenges experienced by adolescents in health research.